2016
DOI: 10.1186/s12992-016-0165-9
|View full text |Cite
|
Sign up to set email alerts
|

Giving Back: A mixed methods study of the contributions of US-Based Nigerian physicians to home country health systems

Abstract: BackgroundThere is increased interest in the capacity of US immigrants to contribute to their homelands via entrepreneurship and philanthropy. However, there has been little research examining how immigrant physicians may support health systems and what factors facilitate or raise barriers to increased support.MethodsThis study used an observational design with paper questionnaire and interview components. Our sample was drawn from attendees of a 2011 conference for US Based Nigerian physicians; respondents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 27 publications
(21 reference statements)
1
20
0
Order By: Relevance
“…Government efforts to provide better healthcare services are yet to be realised [5]. With the globalisation of healthcare, many patients from developed countries in Asia are travelling to Thailand, India and Malaysia for obtaining 'first world treatment at third world prices' [1,6,7,8,9,10,11,12]. Patients from developed and developing countries compare worldwide healthcare service quality, waiting times, cost, post-surgery care, and search for value in healthcare, relative to their own countries.…”
Section: Introductionmentioning
confidence: 99%
“…Government efforts to provide better healthcare services are yet to be realised [5]. With the globalisation of healthcare, many patients from developed countries in Asia are travelling to Thailand, India and Malaysia for obtaining 'first world treatment at third world prices' [1,6,7,8,9,10,11,12]. Patients from developed and developing countries compare worldwide healthcare service quality, waiting times, cost, post-surgery care, and search for value in healthcare, relative to their own countries.…”
Section: Introductionmentioning
confidence: 99%
“…The level of contribution of each medical diaspora organization or individual varies. For instance, while Abdalla et al (2016) reported that the effectiveness of the Sudanese medial diaspora was “small magnitude, infrequent and not well organized [14],” Nwadiuko et al (2016) concluded that U.S.-based Nigerian physicians’ strong belief in effectiveness of Nigerian medical agencies would contribute to medical service trips to Nigeria [15]. In another instance, Wojczewski et al (2015) have shown that African medical doctors who left their home countries as refugees cannot engage in any form of return initiatives, either short or long-term [13].…”
Section: Common Attributesmentioning
confidence: 99%
“…Research is needed to identify strategies that help LMICs retain physicians to serve their populations and train others. Physicians from LMICs who emigrate to HICs often engage in organizing charitable donations, arranging medical missions, assisting with training, as well as helping develop clinical and research programmes. IMPs are encouraged to include these physicians, who possess cultural and language skills, and reconnect them with the healthcare system of their country of origin.…”
Section: The Hic Perspectivementioning
confidence: 99%